2013
DOI: 10.3389/fnins.2013.00128
|View full text |Cite
|
Sign up to set email alerts
|

A paradoxical association of an oxytocin receptor gene polymorphism: early-life adversity and vulnerability to depression

Abstract: Several prosocial behaviors may be influenced by the hormone oxytocin. In line with this perspective, the oxytocin receptor (OXTR) gene single nucleotide polymorphism (SNP), rs53576, has been associated with a broad range of social behaviors. In this regard, the G allele of the OXTR SNP has been accompanied by beneficial attributes such as increased empathy, optimism, and trust. In the current study among university students (N = 288), it was shown that early-life maltreatment was associated with depressive sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
126
6
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 37 publications
22
126
6
4
Order By: Relevance
“…Similarly, the current work found that the frequency of OXTR rs53576 A allele carrier with lower emotional sensitivity can predict the global prevalence of major depression disorder, and this association is mediated by collectivistic cultural values. It has been shown that OXTR rs53576 predicts symptoms of depression and anxiety across individuals (Thompson et al 2014;McQuaid et al 2013). The present work provides macroscale evidence that cultural values play an adaptive role in buffering genetically vulnerable populations from a potentially increasing epidemiological prevalence of mental health disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the current work found that the frequency of OXTR rs53576 A allele carrier with lower emotional sensitivity can predict the global prevalence of major depression disorder, and this association is mediated by collectivistic cultural values. It has been shown that OXTR rs53576 predicts symptoms of depression and anxiety across individuals (Thompson et al 2014;McQuaid et al 2013). The present work provides macroscale evidence that cultural values play an adaptive role in buffering genetically vulnerable populations from a potentially increasing epidemiological prevalence of mental health disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we explored the role of A allelic frequency of OXTR rs53576 in the relationships among pathogen prevalence and individualism-collectivism using a mediation analysis. In addition, given the prior evidence that both 5-HTTLPR and OXTR rs53576 are correlated with depression (Pezawas et al 2005;Thompson et al 2011;McQuaid et al 2013) and that the association between 5-HTTLPR distribution and global prevalence of mood disorders was mediated by individualism-collectivism (Chiao and Blizinsky 2010), we further examined the association among A allelic frequency of OXTR rs53576, individualism-collectivism and prevalence of major depression disorders across nations.…”
Section: Introductionmentioning
confidence: 99%
“…Parte dos estudos incluídos encontrou associação entre a variante rs53576 com sintomas depressivos e depressão (alelo A, genótipos AA, AG e GG). 25,30,34,35 E outros três estudos incluídos encontraram associação estatisticamente significativa entre o genótipo GG do OXTR rs2254298, com sintomas, temperamento depressivo e depressão maior, como pode ser observado na Tabela 1.…”
Section: Conteúdo Da Revisãounclassified
“…Portanto, a determinação dos fenótipos comportamentais é diretamente proporcional à interação gene-ambiente. Os indivíduos portadores de uma ou duas cópias do alelo G parecem ser mais susceptíveis às condições ambientais, sejam elas favoráveis ou não, 37 como pode ser observado no estudo de Mac Quaid et al, 34 no qual os portadores de algum alelo G que sofreram maus tratos na infância de natureza psicológica ou física, apresentaram níveis elevados de sintomas depressivos. Blask et al, 38 ao investigarem a associação de uma população composta por afro-americanos que sofreram maus tratos na infância, verificaram que os indivíduos homozigotos para o alelo G que viviam em um ambiente social favorável apresentavam níveis mais elevados de resiliência e afeto positivo.…”
Section: Artigo De Revisão / Review Articleunclassified
See 1 more Smart Citation